2022
DOI: 10.17957/ijab/15.1912
|View full text |Cite
|
Sign up to set email alerts
|

Oak gall extract: Molecular docking of wound healing and control of the skin pathogens Staphylococcus aureus and Candida albicans

Abstract: Staphylococcus aureus and Candida albicans are common pathogens causing some health problems, however, the increase of their resistance to variety of medications increases the demand of searching for new antimicrobial agents. In this regard, the crude extract of Quercus infectoria (QIE) was verified as active antimicrobial with MBC of 1 mg/mL and MFC 10 mg/mL against S. aureus and C. albicans, respectively. SEM imaging of QIE-Treated-S. aureus and C. albicans cells showed fully lysed shrunk pathogen cells afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It was found that the ultrastructural and morphological changes in the bacteria. Shyma et al also, reported a noticeable reduction in the population of both Staphylococcus aureus and Candida albicans after they had been exposed to the extracted oak galls [ 18 ] . In addition, Dardmah et al showed the positive impact of Quercus infectoria galls on healing open wounds in a streptozocin-induced diabetic BALB/c mouse model [19] .…”
Section: Introductionmentioning
confidence: 95%
“…It was found that the ultrastructural and morphological changes in the bacteria. Shyma et al also, reported a noticeable reduction in the population of both Staphylococcus aureus and Candida albicans after they had been exposed to the extracted oak galls [ 18 ] . In addition, Dardmah et al showed the positive impact of Quercus infectoria galls on healing open wounds in a streptozocin-induced diabetic BALB/c mouse model [19] .…”
Section: Introductionmentioning
confidence: 95%